Enhancing News Text Writing Skills through the RADEC Learning Model: The Role of Reading Interest among Indonesian Vocational High School Students - Yuliarny Yuliarny; Syahrul Ramadhan; Ahmad Johari Sihes; Norliza Jamaluddin (STAI Hubbulwathan Duri, 2025)
Effective writing instruction remains a challenge in Indonesian vocational education, particularly in teaching structured genres like news texts. This study explores the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in improving students’ news text writing skills and examines the moderating role of reading interest. A 2×2 factorial experimental design was implemented with Grade XI students at SMKN 2 Pariaman during the 2024/2025 academic year. A total of 66 students were selected via purposive sampling, with 32 assigned to the experimental group (RADEC instruction) and 34 to the control group (conventional instruction). Instruments included a validated reading interest questionnaire and a performance-based news writing test aligned with curriculum standards. Data were analyzed using independent t-tests and two-way ANOVA. Students in the RADEC group outperformed the control group in writing scores (M = 83.25 vs. 72.15), t(64) = 12.031, p 0.001. The model benefited both high- and low-reading-interest students: high-interest learners in the RADEC group scored higher than those in the control group (M = 83.89 vs. 71.56, t(64) = 3.047, p 0.001), and similar results were found for low-interest students (M = 83.67 vs. 69.56, t(16) = 7.662, p 0.001). However, no significant interaction was found between learning model and reading interest (F(1,32) = 0.16, p = 0.692). The findings highlight the RADEC model’s consistent effectiveness across varying levels of reading interest, positioning it as an inclusive, student-centered strategy for enhancing functional writing in secondary education.